RAVE and Rabconnectin-3 Complexes as Signal Dependent Regulators of Organelle Acidification - Jaskolka, Michael C.; Winkley, Samuel R.; Kane, Patricia M. (Frontiers in Cell and Developmental Biology, 2021)
The yeast RAVE (Regulator of H+-ATPase of Vacuolar and Endosomal membranes) complex and Rabconnectin-3 complexes of higher eukaryotes regulate acidification of organelles such as lysosomes and endosomes by catalyzing V-ATPase assembly. V-ATPases are highly conserved proton pumps consisting of a peripheral V1 subcomplex that contains the sites of ATP hydrolysis, attached to an integral membrane Vo subcomplex that forms the transmembrane proton pore.  Reversible disassembly of the V-ATPase is a conserved regulatory mechanism that occurs in response to multiple signals, serving to tune ATPase activity and compartment acidification to changing extracellular conditions. Signals such as glucose deprivation can induce release of V1 from Vo, which inhibits both ATPase activity and proton transport.  Reassembly of V1 with Vo restores ATP-driven proton transport, but requires assistance of the RAVE or Rabconnectin-3 complexes. Glucose deprivation triggers V-ATPase disassembly in yeast and is accompanied by binding of RAVE to V1 subcomplexes.  Upon glucose readdition, RAVE catalyzes both recruitment of V1 to the vacuolar membrane and its reassembly with Vo.  The RAVE complex can be recruited to the vacuolar membrane by glucose in the absence of V1 subunits, indicating that the interaction between RAVE and the Vo membrane domain is glucose-sensitive.  Yeast RAVE complexes also distinguish between organelle-specific isoforms of the Vo a-subunit and thus regulate distinct V-ATPase subpopulations.  Rabconnectin-3 complexes in higher eukaryotes appear to be functionally equivalent to yeast RAVE.  Originally isolated as a two-subunit complex from rat brain, the Rabconnectin-3 complex has regions of homology with yeast RAVE and was shown to interact with V-ATPase subunits and promote endosomal acidification.  Current understanding of the structure and function of RAVE and Rabconnectin-3 complexes, their interactions with the V-ATPase, their role in signal-dependent modulation of organelle acidification, and their impact on downstream pathways will be discussed.